A qualitative and quantitative study of the reasons of attrition in an Indian hospital - Kasturi Shukla; Ruchismita Deb (Wolters Kluwer Medknow Publications, 2017)
Background: The study attempts to evaluate the reasons of attrition in the organization from the perspective of the existing as well as the leaving employees; compare and identify the gaps, if any between the perspectives of these two employees groups. The study also aims to critically analyze the utility of 'exit interviews' for analyzing the reasons of attrition. Methods: This cross-sectional study was conducted in a 150-bedded hospital in Ahmedabad, India, during May-July 2015. Exit interview data of forty leaving employees were collected and reviewed. One hundred existing employees were interviewed through quantitative and qualitative methods to understand their perceptions about attrition in the organization. Results: Attrition rate of 26% was observed in the study and 57% leaving employees were nurses. 70% leaving employees cite "blanket reasons" such as better opportunity and personal reasons during exit interviews. 72.5% leaving employees believed that exit interview is largely for record purpose and 11% were unsure of its utility. However, when existing employees were probed qualitatively, a variety of responses were received. 65% existing employees quoted salary issues, partiality/poor recognition, improper assignment of tasks, and monotonous work as reasons for attrition in the organization. Conclusion: Exit interviews somewhere fail to probe into the real reasons of attrition. To improve retention, organizations must monitor their existing employee's intention to continue working in the organization and any sign indicating a poor intention to continue must be addressed immediately to avoid ripple effects. Moreover, to use exit interview as a tool to improve employee retention, leaving employees must be interviewed in-depth to uncover the actual reasons for quitting the job.